2020
DOI: 10.1021/acs.biomac.0c00516
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Biohybrid Cellulose Acetate-Collagen Bilayer Matrices as Nanofibrous Spongy Dressing Material for Wound-Healing Application

Abstract: Tissue engineering is currently one the fastest growing engineering fields, requiring fabrication of advanced and multifunctional materials to be used as scaffolds or dressing for tissue regeneration. In this work, a bilayer matrix was fabricated by electrospinning of a hybrid cellulose acetate nanofibers (CA) containing bioactive latex or Ciprofloxacin over highly interconnected collagen (CSPG) 3D matrix previously obtained by a freeze-drying process. The bilayer matrix was fabricated with a nanofibrous part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 65 publications
0
33
0
Order By: Relevance
“…Being able to greatly affect cell migration, oxygen regulation and nutrient exchange, porosity is a key parameter that should be considered during a scaffold design 61 . Usually, in tissue engineering applications, average pore size is measured by the post-processing of SEM micrographs, while total porosity can be calculated separately by liquid displacement method, typically employing ethanol 47 , 62 , 63 . In this work, both total porosity and size pore distribution were inferred from mercury intrusion porosimetry (MIP, see Experimental Methods section) analysis, to ensure that the whole range of sizes presented by these natural, highly-variable materials, could be included (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Being able to greatly affect cell migration, oxygen regulation and nutrient exchange, porosity is a key parameter that should be considered during a scaffold design 61 . Usually, in tissue engineering applications, average pore size is measured by the post-processing of SEM micrographs, while total porosity can be calculated separately by liquid displacement method, typically employing ethanol 47 , 62 , 63 . In this work, both total porosity and size pore distribution were inferred from mercury intrusion porosimetry (MIP, see Experimental Methods section) analysis, to ensure that the whole range of sizes presented by these natural, highly-variable materials, could be included (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Huan’s previous study demonstrates the potential of collagen as cell-culture substrates and cell-delivery vehicles (Chattopadhyay & Raines, 2014 ). Thus, in this study, we incorporated collagen type I into CPCF because it is an important component of the skin, more biocompatible compared to other natural polymers, and exhibits low antigenicity (Ramanathan et al., 2020 ). Results from the MTT assay revealed that CPCF had lower cytotoxicity than that of free curcumin and Cur/PCEC nanoparticles, which are consistent with those from other studies (Hu et al., 2017 ; Yang et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the requirements for wound healing materials such as biocompatibility, oxygen permeability, water absorption, and non-toxicity can be fulfilled by electrospun cellulose-based fabrics. Electrospun CA/collagen nanofibers were incorporated with latex (L) from C. Procera (medicinal plant) for wound-healing, and it was found that CA played an important role in restricting the swelling behaviour and strengthening the fabrics 54 . Similar electrospun CA nanofibers loaded with gelatin and Zataria multiflora (antibacterial plant) could absorb accumulated wound exudates and exhibited good wound healing capacity and antibacterial property 55 .…”
Section: Biomaterialsmentioning
confidence: 99%